Genetic variability and interrelationships of grain yield and its components of selected bread wheat genotypes - Elbashier, Elfadil M. E.; Tahir, Izzat S. A.; Mustafa, Hala. M.; Ibrahim, Abu Elhassan S. (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2018)
High temperature is one of major constraints of bread wheat production in the Sudan. Evaluation of different genotypes under heat stress conditions is one of the main tasks of breeders for exploiting genetic variations to improve cultivars under heat stress. Also, association of yield and yield contributing traits is important for selection. The objective of this study was to evaluate bread wheat genotypes under the irrigated hot environment of the Gezira, Sudan. Experiments were conducted at Gezira Research Farm, Wad Medani, Sudan for two consecutive seasons 2006/07 and 2007/08. The experiments were arranged in an augmented design with six checks, 4 and 12 blocks in the first and second seasons, respectively. Results showed wide ranges of variations in grain yield among these genotypes in both seasons. Grain yield ranged from 965 to 4019 kg/ha and from 133 to 6258 kg/ha in the first and second seasons, respectively. Similar wide ranges of variations were found in biomass, harvest index, number of spikes m -2 , days to heading, days to maturity and plant height. Grain yield showed positive and significant correlation coefficients with biomass and harvest index, in both seasons. Path coefficient analysis indicated that biomass and harvest index were the most directly related parameters to grain yield, in both seasons.